Emotional intelligence and ethical behaviour in mining executives: the mediating effect of trust-building - Edwin Augusto Bashi López; Rubén Guevara Moncada (Cogent Business & Management)
Executives in the mining industry are faced with complex ethical challenges involving the responsible management of resources, environmental impacts, and community relations. As such, it is crucial to understand and develop strategies to enhance ethical behaviour in the mining industry. However, empirical evidence on ethical behaviour among executives in this industry remains limited. This study attempts to address this research gap by analysing the mediating effect of trust-building on the relationship between emotional intelligence and ethical behaviour in mining executives. Partial least squares structural equation modelling (PLS-SEM) was used with a sample of 115 executives at Peru’s largest mining projects, finding that trust-building has a partial mediating effect on the relationship between emotional intelligence and ethical behaviour. Besides adding to the existing academic literature, the results will be useful to mining executives, and possibly to executives in other extractive industries, to focus their efforts in enhancing trust-building to have a larger effect on ethical behaviour in their projects. Furthermore, these results may help when managing relations with different stakeholders, defining and implementing concrete strategies to reinforce ethical behaviour among executives in the mining industry, and probably in other extractive industries, by paying more attention to enhancing emotional intelligence and boosting trust-building in their top and middle-managers and in the workplace.